Post-secondary students communicate about definite integral / Nurhayani Romeo, Roselah Osman and Syarifah Yunus - Romeo, Nurhayani; Osman, Roselah; Yunus, Syarifah (Universiti Teknologi MARA, Sabah, 2024)
Student challenges in learning definite integral are among one of the main issues in calculus. Several cognitive barriers have been identified that cause problems for students when learning for the first time about the single function of the integral. Theory based on radical constructivism is the central pillar in the discussion of this article, and it focuses on the sub-constructs of communication, which identify the description or interpretation essential to students in the definite integral. Students are required to communicate and interpret meaningful sentences that involve the analysis of situations in everyday life. In addition, students also need to communicate by constructing appropriate mathematical sentences according to the information given. There are two categories in communication: the ways students communicate by creating a description that involves definite integrals and how students form sentences from descriptions that involve definite integrals. A case study is the design for the study. The method of selecting respondents is through purposive sampling, which is to choose six second-semester diploma students at technical higher education institutions in the Selangor area, especially those who follow the primary field of technical engineering. The study results show that post-secondary students' understanding of definite integrals certainly involves how they communicate with friends who cannot attend class to learn about definite integrals, which is analyzed based on three categories: mathematical language, skills, and graphics.